(untitled) - Feldman, Richard (Hoboken, N.J., 2008)
Ricochet Confessions Of A Gun Lobbyist. "Ricochet tells the truth. With each page I can hear the echo of footsteps down the Rayburn Building's marbled halls as Feldman tells the intimate story few know and even fewer survive." —Jack Brooks (D-Tex.), former Chairman, U.S. House Judiciary Committee
Keywords: Gun control,Lobbying,Kiểm soát súng,Vận động hành lang; United States,United States,Hoa Kỳ,Hoa Kỳ